Respirometric method for kinetic modeling of ammonium‐oxidizing and nitrite‐oxidizing bacteria in a membrane bioreactor. Issue 8 (2nd June 2020) - Leyva‐Díaz, Juan Carlos; Muñío, Maria del Mar; Fenice, Massimiliano; Poyatos, José Manuel
Abstract: A respirometric method for the kinetic modeling of ammonium‐oxidizing bacteria (AOB) and nitrite‐oxidizing bacteria (NOB) was implemented in two membrane bioreactor (MBRA and MBRB ) systems. These biological systems worked at mixed liquor suspended solids concentration of about 6.6 g L −1 . MBRA worked at 6 hr of hydraulic retention time (HRT) and 20.7°C, while the operational conditions for MBRB were 9.5 hr of HRT and 14.7°C. Experimental data were fitted to the kinetic model with R 2 values of .9320 and .9250 for MBRA and MBRB, respectively. Both systems showed similar performances regarding organic matter and nitrogen removal. However, MBRB showed highest rates of carbon source degradation and net heterotrophic bacteria growth, and MBRA had highest rates of nitrogen source degradation and net autotrophic bacteria growth. This last system was characterized by values for YAOB, YNOB, μm, AOB and μm, NOB of 1.1749 mgVSS mgN −1, 0.6473 mgVSS mgN −1, 0.3664 hr −1 and 0.1823 hr −1, respectively.